Budgetary and financial management reforms in Korea: financial crisis, new public management, and fiscal administration - Ha, Yeon-Seob (2004)
The financial crisis of 1997 has led to a reassessment of the role of the Korean public sector and its management policies. The public sector reforms under the Kim Dae-Jung government (1998-2003) were part of a broader movement toward a more market-oriented economy and lower government debt. One of the core programs of the Korean public sector reform has been the restructuring of budgetary and financial management systems. This article shows that budgetary and financial management reforms during the Kim Dae-jung administration were mostly limited to an emphasis on improving technical efficiency in the delivery of public services through the adoption of market-type mechanisms and several minor improvements in the arrangements for flexible financial management. - Reproduced.
Keywords: Financial administration - Korea; Public administration - Korea; Public finance - Korea; Public finance